2022
DOI: 10.1155/2022/7175027
|View full text |Cite
|
Sign up to set email alerts
|

Transmissible Endoplasmic Reticulum Stress Mediated by Extracellular Vesicles from Adipocyte Promoting the Senescence of Adipose-Derived Mesenchymal Stem Cells in Hypertrophic Obesity

Abstract: Hypertrophic obesity, characterized by an excessive expansion of subcutaneous adipocytes, causes chronic inflammation and insulin resistance. It is the primary feature of obesity in middle-aged and elderly individuals. In the adipose microenvironment, a high level of endoplasmic reticulum (ER) stress and changes in the extracellular vesicle (EV) composition of adipocytes may cause the senescence and restrained differentiation of progenitor cells of adipose, including adipose-derived mesenchymal stem cells (ASC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…17 Moreover, shreds of evidence suggest that the transmissible ER stress is capable of afflicting phenotypic and functional alterations in neighbouring cells, depending largely on the pathophysiological context that triggers endoplasmic reticulum stress activation in donor cells, as well as on the specific cell type undergoing this process. [18][19][20] Exosomes are crucial mediators to exert paracrine effects and can functionally regulate neighbouring or distant recipient cells. 5,21 Heusermann et al 22 indicated that the endoplasmic reticulum of recipient cells might be the principal site of exosome cargo release, as approximately 90% of exosomes have been shown to stagnate at or near the ER.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Moreover, shreds of evidence suggest that the transmissible ER stress is capable of afflicting phenotypic and functional alterations in neighbouring cells, depending largely on the pathophysiological context that triggers endoplasmic reticulum stress activation in donor cells, as well as on the specific cell type undergoing this process. [18][19][20] Exosomes are crucial mediators to exert paracrine effects and can functionally regulate neighbouring or distant recipient cells. 5,21 Heusermann et al 22 indicated that the endoplasmic reticulum of recipient cells might be the principal site of exosome cargo release, as approximately 90% of exosomes have been shown to stagnate at or near the ER.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to nutritional deficiency, renal tubular epithelial cells are susceptible to hypoxia 17 . Moreover, shreds of evidence suggest that the transmissible ER stress is capable of afflicting phenotypic and functional alterations in neighbouring cells, depending largely on the pathophysiological context that triggers endoplasmic reticulum stress activation in donor cells, as well as on the specific cell type undergoing this process 18–20 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is a noticeable connection between the functional aspects of invasion, migration, and ER stress in TNBC. 97,98 Evidence is emerging to suggest that various cellular stresses associated with obesity and tumors play a role in cellular senescence, resulting in accumulation of senescent cells in adipose tissue and various types of cancer.…”
Section: Senescence In the Microenvironment Of Tnbc Patients With Obe...mentioning
confidence: 99%
“…Senescent cells positively impact health span, liver, and vascular tissue fibrosis, and wound healing [119,120]. However, if senescent cells are not cleared within days or weeks by innate immune cells, they accumulate and spread senescence to neighboring and distant cells, mostly via secretion of microRNA-containing vesicles with the consequence of a pro-fibrotic state and deficient tissue function in hypertrophic obesity mice [46,[121][122][123]. Obesity and hyperinsulinemia also drive the senescence of adipocytes or visceral fat macrophages in humans [91,124].…”
Section: Influx Of Immune Cells Into Obese Visceral Fat Inflammation ...mentioning
confidence: 99%